Migraine with brainstem aura: description of a clinical case - D. A. Shmidt; D. S. Golokhvostov; V. V. Osipova; A. R. Artemenko (Неврология, нейропсихиатрия, психосоматика)
The article focuses on a rare form of primary headache – migraine with brainstem aura (previous term – basilar migraine). The place of this form in the International Classification of Headache Disorders is indicated, diagnostic criteria and clinical features are given. Clinical case of migraine with brainstem aura in a young man is presented. The effectiveness of the acute treatment and preventive therapy are discussed; features of the above case are analyzed.